Pediatric diabetic ketoacidosis in a patient with down syndrome. Case report (2019)
Introduction:. Patients with Down syndrome (DS) have an increased risk of developing autoimmune diseases. This is a rare case of a pediatric patient with DS with an initial clinical profile of diabetic ketoacidosis. Case presentation:. 6-year-old male patient with symptoms suggestive of diabetes mellitus type 1 (DM1) of 15 days of evolution (polyuria, polydipsia, polyphagia and loss of 2 kilos of weight), who was admitted to the emergency department of the Hospital de San José, in Bogotá, Colombia, with uncontrollable vomiting and dehydration. The tests performed confirmed moderate ketoacidosis: glycometry: 592 mg/dL, pH: 7.19, HCO3: 10 mmol/L, PCO2: 45, PO2: 95 and lactic acid: 1.4 mmol/L. Management with isotonic fluids and intravenous insulin therapy was initiated and the patient was transferred to the pediatric intensive care unit, where ketoacidosis was controlled in approximately 10 hours. Subcutaneous insulin schedule was initiated without complications. Discussion:. This case highlights the importance of monitoring possible autoimmune complications in patients with DS, since the risk of developing them is 4.2 times higher than in the general population. Conclusion:. This case calls on to contemplate autoimmune complications in patients with DS during clinical practice. Although they are not part of the most frequent reasons for consultation, they cannot be underestimated and should be suspected and treated in a timely manner.